2016
DOI: 10.15639/teflinjournal.v27i2/203-216
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Ability in Using Discourse Markers to Build Coherence in Compositions

Abstract: The study attempts to find out how Indonesian students apply Discourse Markers (DMs) to build coherence in English compositions. It employs a descriptive design, analyzing 52 target DMs and how they are used in 21 argumentative papers. The participants of the study were 21 Master’s students majoring in English Language Teaching (ELT). The results reveal that the participants employ 44 DMs in 234 occurrences, and use some DMs inappropriately in 118 occurrences. The problematic matters cover: non-equivalent exch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Learners did not put the risk of applying grammatical cohesion, which was unaccustomed to them. This was the same as the research by Patriana et al (2016) and Meneveau (2015) that EFL learners feared making errors; thus, they were reluctant to use unfamiliar cohesive devices.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Learners did not put the risk of applying grammatical cohesion, which was unaccustomed to them. This was the same as the research by Patriana et al (2016) and Meneveau (2015) that EFL learners feared making errors; thus, they were reluctant to use unfamiliar cohesive devices.…”
Section: Discussionsupporting
confidence: 76%
“…Cohesive devices enabled readers to capture the meaning between what preceded and what followed. Likewise, Patriana et al (2016) argued that cohesive devices were certain words or phrases and their location within the discourse activated a set of expectations of what might follow. The demonstration to create coherence is a cohesive discourse to make cohesion in writing the text.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mature writing, particularly the academic essays, "requires more than just the ability of writers to create sentences appropriately in the standard language, yet they also need an ability to use cohesive devices to create cohesion and coherence of a text" (Prommas & Sinwongsuwat, 2011, p. 2; see also Das & Taboada, 2018;Patriana et al, 2016). Coherence refers to the unity of the ideas and cohesion the unity of structural elements (Chalmers Writing Centre, n.d.).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies conducted by Kao and Chen (2011) proposed six problems encountered by Taiwanese students, namely: non-equivalent exchange, overuse, surface logic, wrong relations, semantic inclusions, and disturbances. In Indonesia, a study conducted by Patriana, Rachmajanti, and Mukminatien (2016) which analyzed the use of 21 students' argumentative markers of argumentative essays by Indonesian students found that in 234 occurrences, 118 occurrences used DM improperly.…”
Section: Introductionmentioning
confidence: 99%